Rice husk modification via esterification for Palm Oil Mill Effluent (POME): article - Aziz, Wan Nur Shafikah; Alias, Nor Halaliza (2017)
Palm Oil Mill Effluent (POME) is a colloidal suspension originating from a mixture of sterilizer condensate, separator sludge and hydro-cyclone wastewater which is thick brownish colloidal mixture of water, oil and fine suspended solids when it is fresh. POME produced from industry contains higher amount of Chemical Oxygen demand (COD), Biological Oxygen Demand (BOD), Suspended Solid (SS) and oil and grease which over limit the standard set by the Government Agency which is Department of Environment (DOE). POME is categorized as a serious problem towards the environment as it can cause the reduction of oxygen in water thus affected the river and aquatic life when there are excessive amount of untreated POME. Due to this case, many methods have been conducted in treating the POME such as membrane technology, adsorption, and single stage ponding system. Adsorption is considered as an effective method because it is simple, applicable and low cost technique in treating the POME. Thus, the adsorption was selected by using the natural adsorbent which is rice husk for POME treatment. The rice husk was chosen because of its simple accessibility and most abundant biodegradable. The rice husk was modified via esterification process by an effective mass of stearic acid, CH₃(CH₂)₁₆COOH in order to improved its hydrophobicity character. The effects of percentage of calcium oxide, CaO added and ratio of rice husk to stearic acid on the capacity of oil adsorption were investigated. The parameters that have been varied during the experiment were the percentage of calcium oxide added (5 % and 10 %) and ratio of rice husk to stearic acid (1:1, 1:4 and 1:7). Oil adsorption test was carried out in order to characterize the esterified rice husk in removal of oil from POME thus increased in oil adsorption capacity. The optimum operating condition of esterified rice husk was obtained at ratio of 1:7 rice husk to stearic acid and 5 % of calcium oxide added into the reaction as it successfully increased the oil adsorption for the removal of oil from POME at 0.1992 g/g. In addition, the high adsorption capacity of modified rice husk was better than unmodified rice husk as a result of increasing from 0.0824 g/g (40 %) to 0.1992 g/g (96.7%).